A Wide‐Range Linear and Stable Piezoresistive Sensor Based on Methylcellulose‐Reinforced, Lamellar, and Wrinkled Graphene Aerogels. Issue 5 (19th October 2021) - Li, Guochen; Chu, Zengyong; Gong, Xiaofeng; Xiao, Min; Dong, Qichao; Zhao, Zhenkai; Hu, Tianjiao; Zhang, Ye; Wang, Jing; Tan, Yinlong; Jiang, Zhenhua
Abstract: Graphene‐based aerogels (GAs) have been extensively studied for pressure sensing applications due to their high compressibility and conductivity. But the usually‐adopted high‐temperature treatment generally damages the flexibility and stability. It is still challenging to prepare piezoresistive sensors with a wide linear range, and reliable cyclic performance. Herein, we demonstrate an excellent wide‐range piezoresistive sensor based on an aerogel of methylcellulose reinforced reduced graphene oxide (MC/GA). A steaming reduction at 120 °C is proposed to properly control the intermolecular forces and the chemical bonding between MC and GA. The finite element analysis indicates that wrinkled lamellae with hierarchical pores are beneficial to minimize the stress concentrations. As a result of the combined architecture of reinforced, oriented, and wrinkled lamellae with hierarchical pores, the MC/GA has a superior linearity in a much wide range (0–17 kPa, R 2  > 0.997), a high sensitivity (9.38 kPa −1 ), a short response time (<40 ms) and a reliable cyclic performance (>99% retention). As demonstrations, the MC/GA sensor can monitor vital signs of the upper lip, throat or wrist, and can sense the large motion of the fingers, elbows, and feet. These advantages make the MC/GA sensor have a great potential in various health monitoring and motion‐detecting fields. Abstract : A graphene aerogel with wrinkled and lamellar architecture is prepared from methylcellulose and graphene oxide through directional freezing, freeze‐drying, and steaming reduction. When assembled as a piezoresistive sensor, the aerogel exhibits a wide range of linearity and very good stability, demonstrating great potential in the detection of both vital and large motions.